Clinical Testing of a New Radiopharmaceutical [99mТс]-Al2O3 for the Diagnosis of Sentinel Lymph Nodes - А. A. Medvedeva; V. I. Chernov; R. V. Zelchan; O. D. Bragina; A. A. Rybina; V. S. Skuridin; E. S. Stasyuk; S. Yu. Chizhevskaya; A. V. Goldberg; E. Yu. Garbukov (Разработка и регистрация лекарственных средств)
Introduction. In modern oncology, the identification of sentinel lymph nodes (SLN), the first nodes that stand on the way of malignant tumor metastasis, is of increasing interest. Detection of SLN followed by morphological examination allows personalizing the surgical intervention for early breast cancer, melanoma, head and neck tumors, neoplasms of the cervix and endometrium. Currently, there is an active development of specific radiopharmaceuticals for SLN imaging. Within the framework of the grant from the Federal Target Program "Pharma-2020", an original radiopharmaceutical using gamma aluminum oxide – [99mТс]-Al2O3 was developed. Preclinical studies have been demonstrated its effectiveness and safety. Pharmacokinetic studies of [99mTc]-Al2O3 showed that 24 hours after its subcutaneous administration, about 12 % of the administered dose is accumulated in the SLN, which gives possibility for its detection.Aim. To study the possibility of clinical [99mTc]-Al2O3 using for visualization of SLN in breast, larynx and laryngopharyngeal cancer.Materials and methods. The definition of SLN was carried out in 55 patients with breast cancer and 30 patients with malignant tumors of the larynx and laryngopharynx. The study included peritumoral radiopharmaceutical injection, single-photon emission computed tomography with qualitative and quantitative analysis of the images and radioguided surgery detection of lymph nodes with their subsequent morphological examination.Results and discussion. Clinical studies have shown that radionuclide imaging of SLN using [99mTc]-Al2O3 is characterized by high sensitivity in breast cancer, larynx and laryngopharyngeal cancer patients (94.5 and 90 %, respectively), due to the high-intensity accumulation of this radiopharmaceutical in the lymph nodes. The optimal time point for SPECT and radioguided examination is an interval of 18–20 hours after injection of [99mTc]-Al2O3, which allows visualizing the maximum possible number of lymph nodes with the most optimal level of radioactivity for their detection.Conclusion. Application of radionuclide imaging of SLN with the use of [99mTc]-Al2O3 as a radiopharmaceutical is useful in planning surgical treatment of patients with tumors of the breast, larynx and laryngopharynx to determine the extent of surgery.